AI Technologies in STEAM Education for Students: Systematic Literature Review - Al-Zahrani, Amirah; Khalil, Ibrahim; Awaji, Bakri; Mohsen, Mohammed (Journal of Ecohumanism, 2024)
This study aimed to identify trends in the research conducted on Artificial Intelligence (AI) in STEAM (Science, Technology, Engineering, Arts, and Mathematics) education. To achieve this goal, a total of 16 articles were reviewed from the Web of Science (WOS) database. The analysis revealed an increase in the number of educational AI studies in 2021 and 2022, with Spain and South Korea emerging as the leading countries in implementing AI technologies in STEAM (Science, Technology, Engineering, Arts, and Mathematics) education. Quantitative research methods were predominantly employed in the reviewed articles, and most of the studies focused on primary and secondary students as the target sample. Among the various AI applications, educational robots were found to be the most commonly utilized in STEAM education. The findings of the study demonstrated that AI technologies contribute to the development of thinking skills, such as computational and analytical thinking, enhance self-confidence, increase satisfaction and enjoyment among students, and also deepen their understanding of STEAM concepts. These insights have important implications for teachers, practitioners, and policymakers in making informed decisions regarding the effective integration of AI in STEAM education. Furthermore, the results obtained in this study are expected to guide future research in this field.